Writing Strategy: an Analysis of Successful Malahayati English Council Learners in Writing - Aiyub Aiyub; Putri Dini Meutia; Suryani Suryani; Ema Dauyah (IAIN Manado, 2022)
Writing Strategy: an Analysis Of Successful Malahayati English Council Learners in Writing. The purpose of this study is to discover what kinds of learning strategies are used by successful learners to improve their English writing skills. This study employed an explanatory mixed method. A questionnaire is an instrument used to collect data. The population in this study was Malahayati English Council students enrolled in writing classes, and the sample consisted of students who earned an A (86-100) in the final writing subject. The data was analyzed using a simple statistic and the cumulative frequency distribution method. Based on the result of this study, it was concluded that first, Writing is a continuous process of thinking, organizing, rethinking, and reorganizing. It requires command of vocabulary, spelling, grammar, punctuation, appropriate content, and word selection for the audience, topic, and occasion. A writer must be able to think and express ideas in well-organized sentences with high coherence. Second, successful learners applied the writing strategies those are suggested by the expert. They used those strategies to solve all problems and to get the best results in writing. Third, the strategy employed is to divide the writing process into four stages: prewriting, drafting, revising, and editing